Human Herpesvirus type 6 infection related to dermatological manifestations and chronic fatigue: case series - Ávila-González, Gloria Inés; Erazo-Narváez, Andrés Felipe; Sánchez-Muñoz, Fernando; Riascos-Montes, Rigobert Alexis; Anacona, Cristian; Dueñas-Cuellar, Rosa Amalia; Niño-Castaño, Victoria Eugenia; Klínger, Julio César (Universidad y Salud, 2020)
Introduction: The most frequent clinical manifestations of Human Herpesvirus 6 (HHV-6) in children under 2 years of age are roseola-like skin lesions and sudden rash. In adults, the clinical manifestations associated with HHV-6 are highly variable and can overlap with other conditions. Objective: To present a case series of patients diagnosed with active HHV-6 infection, who showed neurological, dermatological and chronic fatigue manifestations. Materials and methods: An analysis of medical records of 6 patients who were diagnosed with active HHV-6 infection through molecular methods was performed. Results: 6 patients were diagnosed with active HHV-6 infection using molecular methods, who had common clinical manifestations such as fever, headache, depression, tiredness, loss of memory and concentration, fibromuscular pain, polyarticular pain, nonrestorative sleep, rash, ruby nevus, lichen planus and paresthesia. Conclusions: This case series highlights the importance of identifying active HHV-6 infection through molecular methods and creating awareness in the medical community of the role that the virus plays on the development of diverse pathologies.